Factors associated with stock out of malaria test kit in Oshana region, Namibia - Emmanuel Magesa; Kabwebwe Honore Mitonga; Penehafo Angula (AOSIS, 2020)
Malaria continues to be a serious communicable disease whose impact on public health in Namibia is massive. Some improvement in reducing the number of malaria cases has been made in the country, but the sporadic availability of malaria diagnostic test kits (mRDT) continues to slow down government efforts to eliminate malaria in the country. Given the nature of current conditions, justification exists for a study to determine the factors associated with stock out of malaria rapid test kit (mRDT) in Namibia. Mixed method approach was employed, whereby in quantitative aspect, the study adopted a descriptive approach to acquire data from a period of five years retrospectively (2012 - 2016). To gain insight into qualitative aspects of the study, key informants at all levels of the supply chain in Oshana region were interviewed. Pharmaceutical knowledge of ordering mRDT is needed to prevent stock out of mRDT. It is a recommendation of this study that training is needed for staffs who are involved in ordering of pharmaceutical items.